Investigation of comprehensive methods for combating asphaltene-resin-paraffin deposits in oil production operations - Semenenko D. S. (НТУ «ДП», 2025)
In the context of developing multilayer hydrocarbon reservoirs in Ukraine, particularly in the Dnieper-Donets Basin, the simultaneous-separate exploitation (SSE) technology enables efficient extraction from multiple horizons through a single wellbore, reducing capital expenditures on drilling and infrastructure. However, this approach is complicated by the intensive formation of asphaltene-resin-paraffin deposits (ARPD), which accumulate in tubing, near-wellbore zones, and surface equipment. These deposits lead to a 50% reduction in flow rates within 3–6 months, increased energy consumption, and frequent failures, with inter-cleaning periods as short as 45–150 days in high-paraffin oils (paraffin content >6% by mass) and flow rates below 50 t/day [1, 2].
Keywords: асфальтеново-смоло-парафінові відкладки; нафтовідбиткові операції; буріння